Implementasi Aplikasi Bank Dokumen untuk Manajemen Arsip pada Lembaga Pendidikan dan Bidang Kesehatan ICFAM dengan Metode RAD - Amru, Muhamad Tegar; Ramadhan, Caesar Ariel; Fahriza, Febri Eka; Haryono, Wasis (Sublim: Jurnal Pendidikan, 2025)
In the digital era, the need for efficient, secure, and accessible document management is increasingly critical, particularly in the education and health sectors. ICFAM still relies on manual archiving systems, resulting in slow document retrieval, data loss risks, and limited collaboration among users. To address these issues, a Document Bank application was developed using the Rapid Application Development (RAD) method. This method supports fast and flexible system development by involving users directly in each stage. The study adopts a descriptive approach, utilizing observation, interviews, and literature review as data collection techniques. The results show that the application significantly improves operational efficiency, enhances document security, and supports transparency and information accountability within ICFAM.